2012
DOI: 10.35196/rfm.2012.2.171
|View full text |Cite
|
Sign up to set email alerts
|

COMPOSICIÓN QUÍMICA DE TALLOS INMADUROS DE Acanthocereus spp. E Hylocereus undatus (Haw.) Britton & Rose

Abstract: Los tallos inmaduros de cruceta o jacube (Acanthocereus tetragonus), nopal de cruz (A. subinermis) y pitahaya (Hylocereus undatus) son de consistencia suave y se utilizan en la gastronomía mexicana; pero hay poca información sobre su contenido nutrimental. El objetivo de este trabajo fue determinar la composición proximal y mineral de sus tallos tiernos. El material vegetal se recolectó de una plantación experimental ubicada en Tepoztlán, estado de Morelos, México. Los resultados obtenidos se expresaron en bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Regarding to the content of mineral microelements for pitahaya fruits, the content of manganese (5.48 ± 0.1 mg.kg -1 ) and zinc (5.39 ± 0.25 mg.kg -1 ) for red pitahaya stand out; and in the case of the yellow pitahaya, the highest values corresponded to iron (21.07 ± 0.18 mg.kg -1 ) and manganese (7.49 ± 1.12 mg.kg -1 ). Juárez-Cruz et al (2012), found important values of the minerals of zinc and potassium (34.02 mg.kg -1 and 4.82 g.100 g -1 , expressed on a dry basis, respectively), for tender stems of the Hylocereus undatus variety from Mexico.…”
Section: Resultsmentioning
confidence: 94%
“…Regarding to the content of mineral microelements for pitahaya fruits, the content of manganese (5.48 ± 0.1 mg.kg -1 ) and zinc (5.39 ± 0.25 mg.kg -1 ) for red pitahaya stand out; and in the case of the yellow pitahaya, the highest values corresponded to iron (21.07 ± 0.18 mg.kg -1 ) and manganese (7.49 ± 1.12 mg.kg -1 ). Juárez-Cruz et al (2012), found important values of the minerals of zinc and potassium (34.02 mg.kg -1 and 4.82 g.100 g -1 , expressed on a dry basis, respectively), for tender stems of the Hylocereus undatus variety from Mexico.…”
Section: Resultsmentioning
confidence: 94%
“…Sin embargo, para el caso de Mg, en todos los tratamientos donde se utilizó vermicompost, la concentración fue menor que la del testigo con solo riego y solo fertirriego con NPK (Tabla 6). Estos resultados concuerdan con Juárez- Cruz et al (2012), al determinar altos contenidos de K y Zn en H. undatus; además Granados y Castañeda (1996) han señalado que entre los principales macronutrimentos de las cactáceas se encuentran el calcio y el potasio, aunque al determinarse el contenido nutrimental de las plantas, la edad o su estado fenológico puede ser un factor de variación (Guzmán y Chávez, 2007). De igual forma, la incorporación de vermicompost de estiércol bovino en plantas de menta (Mentha piperita L.), incrementó la concentración de NO3y K + en los tallos de las hojas (Romero et al, 2013).…”
Section: Contenido Nutrimental De Tallos De Pitahaya De Pulpa Roja Y ...unclassified
“…A. tetragonus is traditionally collected from wild populations, and the young stems are sold at prices of around USD 1 per 150 g of fresh chopped young stems in local markets and urban venues (see Figure 1a-c), especially in the state of Veracruz, Mexico [12], where they represent a source of alternative food in some isolated regions. Regarding their chemical composition, it has been demonstrated that they are rich in proteins, fiber, and minerals such as phosphorus, potassium, magnesium, sodium, and copper, in addition to containing a high level of calcium [13]; nevertheless, as far as we know, no information exists regarding the phytochemical profile of A. tetragonus. In this study, we analyzed, by means of Ultra-High-Performance Liquid Chromatography coupled to High-Resolution Mass Spectrometry (UHPLC-PDA-HESI-Orbitrap-MS/MS), the phytochemical profile of cooked and crude samples of A. tetragonus to assess its functional metabolite contribution to the human diet.…”
Section: Introductionmentioning
confidence: 99%